Molecular Docking of Quercetin for Inhibition of Enoyl-Acyl Carrier Protein Reductase in Mycobacterium tuberculosis - Irfandi, Rizal (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Tuberculosis remains a global health issue, with treatment hindered by drug resistance. This study aims to identify the potential of Quercetin as an inhibitor of Enoyl-Acyl Carrier Protein Reductase (M. tuberculosis), a key enzyme in the fatty acid biosynthesis of the bacteria. Using molecular docking, Quercetin is evaluated based on its binding affinity and stability with the target protein. The docking results show that Quercetin binds to the active site of Enoyl-Acyl Carrier Protein Reductase through hydrogen bonds, π-alkyl, and π-sigma interactions, with an RMSD value of 1.6466 Å, indicating valid results. Comparison with the control compound, 5-hexyl-2-(2-methylphenoxy)phenol, reveals that Quercetin has a stronger binding affinity, supporting its potential as a more effective enzyme inhibitor. These findings open new opportunities for the development of natural compound-based anti-Tuberculosis therapies that can address the growing problem of drug resistance. Further research is needed for experimental validation in biological models and the development of more efficient Quercetin formulations.